EKSPLORASI MAKANAN TRADISIONAL BALI DI KABUPATEN BANGLI - A.A Ketut Pujawan; Ni Putu Eka Trisdayanti (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2017)
Traditional Balinese food is one of the nation’s cultures inherited by the ancestors that are increasingly eroded and will slowly be abandoned. In view of these facts, the traditional Balinese food needs to be explored for inventory and documentation that can later be preserved and introduced to local and international communities to strengthen the nation’s identity. In this research, the object of research is the traditional culinary in Bangli regency. The location of the data was collected in all subdistricts in Bangli District, Bangli Subdistrict, Susut Subdistrict, Tembuku Subdistrict, and Kintamani District. Data collection is done in traditional markets, where traditional culinary sellers, at home. The technique of collecting data of this research that is by way of a survey. The survey conducted interviews with producers who produce/sell the traditional food. The survey was conducted by visiting and interviewing respondents directly by using a list of questions of information desired from the respondents, especially regarding the names of the traditional foods being processed, the materials used, and the processing. Data analysis technique of this research is descriptive qualitative. Based on the research result, the number of Balinese traditional food in Regency of Bangli counted 90 species, consisting of 4 types (4,4%) main food, 47 kinds (52,2%) side dish consisting of 40,4% vegetable side dishes And 59.6% of animal products, 34 types (37.8%) of snack, and 5 (5.6%) beverages. The ingredients used in this traditional culinary manufacture are sourced from the local (local) area, but there are also some ingredients sourced from other regions. Regarding the processing of traditional culinary in Bangli regency, the method used is still traditional. In addition, the method used is still hereditary without referring to the recipe and still use the habit. The cooking methods used in traditional culinary making in Bangli Sub-district consist of: steamed, boiled, baked, pan-fried, and fried. However, some traditional culinary in Bangli regency is processed without using cooking process, such as in making some beverages, such as loloh cemcem, loloh turmeric and daluman where the ingredients are used only water is taken only.